PENGARUH KUALITAS PELAYANAN TERHADAP MINAT MENABUNG DI BAITUL MAAL WAT TAMWIL KOPERASISIMPAN PINJAM PEMBIAYAAN SYARIAH INDRAGIRI HULU - Syafaruddin, Tia Safitri (JURNAL ISLAMIKA, 2023)
The purpose of this study was to prove the effect of service quality on people's interest in saving at the Baitul Maal Wat Tamwil Islamic Savings and Loans Cooperative Indragiri Hulu. This study uses a quantitative method with a customer population of Baitul Maal Wat Tamwil Indragiri Hulu as many as 5,452 customers and a sample of 98 customers. The data sources used are primary data and secondary data. The technique used is used to determine the sample using the Slovin formula. Data were processed and analyzed using simple linear regression and using SPSS 26.0 for Windows. The research results of the coefficient of determination test show that with an R Square value of 0.600, a coefficient of determination value of 60% is obtained. These results show that the influence of the independent variable, namely Service Quality, on Interest in Saving is 0.600 or 60%. Meanwhile, the remaining 40% is influenced by other variables not examined in this research. And the results of (t-test) if seen from the tcount value is 12.005. Meanwhile, ttable with a significance level of 5% and df = 98 -2 = 96 obtained a ttable value of 1.985. Based on these results because tcount > ttable (12.005 > 1.984) then H0 is rejected and H1 is accepted, which means that there is a significant influence between Service Quality on Saving Interest."